SOLIDARITAS POKJA MASYARAKAT HADAPI POTENSI TSUNAMI MELALUI WADAH DESTANA - Rodhy Fathul Muzib; Baiq Lily Handayani; Joko Mulyono (Universitas Wijaya Kusuma Surabaya, 2021)
This article will talk about solidarity formed by grous society, whe they have same goal to build a social programs and mobilizing the community to care about potential threats Tsunami disaster in Sarongan Village. This research uses research methods qualitative by using a case study approach, as well as using techniques in-depth interviews for the data collection process. Based on the results research shows that there are resources found in group a society where they consolidate each other by building relationships cooperation betweencommunity groups based on social ideology humanity. A social program carried out by the Sarongan community group formed on the basis of te factor of similarity of beliefs seen in conciousness people who care about disasters. The formation of the latter social mobilizing resources, giving rise to disaster response social programs aimed at tackling potential disaster. Social grup such as, Coral Taruna, PKK, and several Village Institutions work together for latter carry out a collective action in Tsunami disaster management as well forming a Disaster Risk Management Forum with the aim of to be a responsive forum in the process of socializing disaster for people public. This is where community’s Working Group was formed then by BNPB formed Destana where It’s membership consists of representative of village community group management Sarongan. Keywords: Disaster, Resource Mobilization, Solidarity, Tsunami